2019
DOI: 10.1136/archdischild-2019-317830
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental impairment in necrotising enterocolitis survivors: systematic review and meta-analysis

Abstract: AimTo determine (1) the incidence of neurodevelopmental impairment (NDI) in necrotising enterocolitis (NEC), (2) the impact of NEC severity on NDI in these babies and (3) the cerebral lesions found in babies with NEC.MethodsSystematic review: three independent investigators searched for studies reporting infants with NDI and a history of NEC (PubMed, Medline, Cochrane Collaboration, Scopus). Meta-analysis: using RevMan V.5.3, we compared NDI incidence and type of cerebral lesions between NEC infants versus pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 85 publications
0
41
0
Order By: Relevance
“…While many of these infants met the classic definitions of "extrauterine growth failure" or "postnatal growth failure" (weight < 10th percentile at discharge), experts have recently suggested that other growth metrics are more important for predicting neurodevelopmental outcomes [12]. Postnatal head-sparing growth may be critical to optimize neurodevelopment, and this is important as infants with NEC are at risk for neurodevelopmental impairment [13][14][15][16]. These results are consistent with previous studies which demonstrated that preterm infants with surgical NEC have growth failure at 18-24 months [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…While many of these infants met the classic definitions of "extrauterine growth failure" or "postnatal growth failure" (weight < 10th percentile at discharge), experts have recently suggested that other growth metrics are more important for predicting neurodevelopmental outcomes [12]. Postnatal head-sparing growth may be critical to optimize neurodevelopment, and this is important as infants with NEC are at risk for neurodevelopmental impairment [13][14][15][16]. These results are consistent with previous studies which demonstrated that preterm infants with surgical NEC have growth failure at 18-24 months [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…With ‘improving’ survival now achieved by surgery in the sickest NEC babies, key findings of the ORACLE study 22 and Matei et al's 23 recent publication are worthy of mention in closing. These reports clearly show the long‐term consequences of NEC on gut function, motor, sensory, and neurodevelopmental/cognitive outcome(s) highlighting the significant morbidity on patient quality of life.…”
Section: Discussionmentioning
confidence: 96%
“…The authors also adjusted for necrotizing enterocolitis (NEC). However, NEC partially mediates the association between the EHM and PVL [4,5]. Controlling NEC would be inappropriate as it would partially close the indirect causal path, thereby attenuating the observed association between EHM and IVH or PVL (overadjustment bias) [2,3].…”
Section: To the Editormentioning
confidence: 99%